1985
DOI: 10.1002/bjs.1800720327
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystectomy in the elderly: A prospective study

Abstract: The mortality and morbidity of 151 elderly patients (greater than 64 years of age) undergoing biliary surgery for benign disease were prospectively studied. The overall mortality was 3.3 per cent. This comprised a 0.77 per cent mortality in the elective group and a 19 per cent mortality in the emergency group. In spite of 77 per cent of the emergency group having a gangrenous gallbladder, a complication difficult to predict preoperatively, the majority of deaths were from cardiovascular disease. The overall in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
54
2
3

Year Published

1986
1986
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(61 citation statements)
references
References 25 publications
2
54
2
3
Order By: Relevance
“…Urgent or early cholecystectomy is the standard therapy for acute cholecystitis (1,2). Cholecystectomy is generally a safe procedure, but the surgical risk is high in patients with severe medical or surgical comorbidities (3). In such high-risk patients, percutaneous der stenting (EGBS) is a promising alternative treatment option for critically ill patients with symptomatic acute cholecystitis (10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Urgent or early cholecystectomy is the standard therapy for acute cholecystitis (1,2). Cholecystectomy is generally a safe procedure, but the surgical risk is high in patients with severe medical or surgical comorbidities (3). In such high-risk patients, percutaneous der stenting (EGBS) is a promising alternative treatment option for critically ill patients with symptomatic acute cholecystitis (10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Although cholecystectomy is considered a safe operation in most patients with cholecystitis, the morbidity and mortality of this procedure increase considerably in elderly patients at high risk, including patients with cardiopulmonary or renal disease, sepsis, or multiorgan failure (3). In such cases, conservative measures such as performing a percutaneous cholecystostomy, which permits an interval cholecystectomy or cholecystolithotomy, can be considered as an alternative to minimize surgical and anesthetic trauma (1).…”
mentioning
confidence: 99%
“…There was no operative death in this small series. Reported mortality ranges from less than 1% for patients less than 60 years of age to 6.7% for patients 60 years or older [10,[14][15][16]. Wound infection of 1% in this study falls within reported limits of up to 7% [1,7].…”
Section: Discussionmentioning
confidence: 51%